Gluten-sensitive Enteropathy: INFLUENCE OF HISTOCOMPATIBILITY TYPE ON GLUTEN SENSITIVITY IN VITRO - Falchuk, Z. M. (1980)
We previously developed an in vitro organ culture system in which gluten exerts a toxic effect on intestinal mucosa of patients with active gluten-sensitive enteropathy. Gluten generally inhibits the epithelial cell maturation of intestinal biopsy specimens that otherwise occurs if the tissue is cultured for 24-48 h in a gluten-free medium. However, small intestinal mucosa from 15-20% of patients with proven gluten-sensitive enteropathy fails to manifest the expected gluten-induced damage in vitro. In the present study, we explored the relation between in vitro gluten-induced intestinal damage and the presence of HLA-B8. We determined whether the patients' histocompatibility type (HLA-B8 positive or negative) influenced the ability of gluten protein to inhibit epithelial cell maturation of cultured intestinal biopsy specimens from patients with gluten-sensitive enteropathy. Intestinal biopsies from 21 of 24 patients with gluten-sensitive enteropathy and HLA-B8 showed gluten-induced damage in vitro. On the other hand, intestinal biopsies from only 4 of 16 patients with gluten-sensitive enteropathy but without HLA-B8 showed gluten-induced damage in vitro. The difference in the effect of gluten in vitro between these two groups was statistically significant (P < 0.01). The data show a dichotomy between gluten-induced tissue damage in vivo and in vitro in HLA-B8 negative patients, suggesting that HLA-B8 is important for gluten to manifest a cytotoxic influence in organ culture.